New York State Breast Density Mandate: Follow‐up Data With Screening Sonography. (28th June 2017) - Destounis, Stamatia; Arieno, Andrea; Morgan, Renee
Abstract : Objectives: To evaluate the impact on breast cancer detection from screening breast sonography performed in women with mammographically dense breasts. Methods: This study used a retrospective chart review. Data collected included total number of screening mammograms, total number of dense breast screening sonograms, total number of procedures performed, biopsy results, and demographic data. Data were obtained from January 1, 2013, through August 31, 2015. During this period, there were a total of 195, 982 screening mammographic examinations performed at our facility. Of these, 83, 234 patients (42.5%) were informed that their breast tissue was heterogeneously dense or extremely dense. We specifically reviewed cases to identify those with findings on sonography only. The positive predictive value, biopsy rate, and cancer detection rate were determined. Results: During the study period, 5434 screening sonographic examinations were performed in 4898 women with heterogeneously dense or extremely dense breasts. Most (95.7%) of the sonographic examinations resulted in an American College of Radiology Breast Imaging Reporting and Data System (BI‐RADS) category 1 or 2 designation. A total of 101 lesions were given a BI‐RADS 3 designation; 134 suspicious findings were given a BI‐RADS 4 or 5 designation; and 100 of these were seen on sonography only, all of which underwent tissue sampling, resulting in the diagnosis of 18 malignancies; all were invasive. In evaluating screening sonographic findings, we found a positive predictive value of 18.0%, with an overall biopsy rate of 2.0% and a cancer detection rate of 3.3 per 1000. Conclusions: The results of our continued evaluation of our screening sonography program confirm that screening breast sonography in women with dense breast tissue can detect otherwise occult malignancy, with a low biopsy rate.